Strengthening Hospital Care Quality through Patient Safety Education: Evidence from a Regional Hospital in Eastern Indonesia - Feby Manuhutu; Dene Fries Sumah; Vanny Leutualy; Valensya Yeslin Tomasoa; Syulce Luselya Tubalawony; Nenny Parinussa; Hery Jotlely; Olivia Talahatu (Karya Kesehatan Siwalima, 2026)
Patient safety is an essential component in improving the quality of healthcare services. The World Health Organization, through the Global Patient Safety Action Plan 2021–2030, emphasizes the importance of healthcare systems that prioritize patient safety. However, the implementation of patient safety practices in hospitals continues to face several challenges, including limited knowledge among healthcare workers and a low culture of incident reporting. This community service activity was conducted by nursing lecturers at a regional hospital and involved 60 nurses. The methods employed included interactive lectures, group discussions, and practical simulations based on the six International Patient Safety Goals. Evaluation was carried out using pre-tests and post-tests. The results demonstrated a significant improvement in knowledge, with the average score increasing from 56% to 87%. Patient safety education was proven to be effective in enhancing nurses’ understanding and awareness, thereby strengthening the culture of patient safety and improving the overall quality of healthcare services in hospitals.